GREEN SYNTHESIS OF ZINC OXIDE NANOPARTICLES USING SCHREBERA SWIETENIOIDES ROXB., AQUEOUS LEAF EXTRACT AND INVESTIGATION OF ITS EFFECT ON SEED GERMINATION AND PLANT GROWTH ON PIGEON PEA (CAJANUS CAJAN LINN.) - TULASI, S. LAKSHMI; SWAMY, A. V. V. S.; PAVANI, P.; SUBHASHINI, V. (International Journal of Applied Pharmaceutics, 2022)
Objective: The present work intended to green and eco-friendly synthesis of Zinc oxide (ZnO) nano particles (NPs) using aqueous leaf extract of Schrebera swietenioides and the synthesised NPs were applied for enhancement of seed germination and plant growth in pigeon pea (Cajanus cajan Linn.). Methods: The Zinc acetate was utilised as metal source and metal was reduced using aqueous leaf extract of S. swietenioides as green reducing agent. The synthesised NPs were characterized using various techniques such as SEM-EDS, TEM, XRD, FT-IR and UV-visible spectrophotometer. The seed germination study as well as plant growth promotion activity, was performed on pigeon pea seeds. Results: The result achieved in characterization of NPs confirms that he NPs were hexagonal wurtzite form having a spherical shape with irregular surfaces. The average size was found to be 68 nm with the metal composition of 73.7 %. The NPs were studied for seed germination and growth promotion activity on pigeon pea seeds and the mean germination time was observed to be 38.60±0.56, 28.53±0.59 and 37.53±0.40 h whereas the final germination percentage was found as 91.33±0.58, 98.00±1.00, and 92.67±1.15 h for control, NPs treated and zinc acetate treated seeds respectively. The NPs treated plants grow more rapidly than the untreated as well as Zn acetate-treated pigeon pea plants. The pigeon pea seeds treated with ZnO NPs shows the high activity of enzyme activities such as amylases, protease, catalase than the untreated as well as Zn acetate treated seeds. Conclusion: The aqueous leaf extract of S. swietenioides mediated ZnO NPs can augment the growth of pigeon pea seedlings, and the NPs treatment shows a stimulatory effect on the enzymes associated with the growth of seedlings.